Electronic properties of LiNbO3 using density functional theory/ L. W. Zainuddin, O. H. Hassan and M. F. M. Taib - Zainuddin, Lili Widarti; Hassan, O.H.; Taib, M.F.M. (2023)
Using the density functional theory, the structural and electronic properties of LiNbO3 are investigated. The lattice constants and unit cell volume were calculated from the optimized unit cell, which were in well agreement with the reported theoretical as well as experimental values. Electronic band structure and density of states (DOS) demonstrated its semiconducting nature showing a band gap of 3.504 eV.